IMPLEMENTASI APLIKASI ANTRIAN PENGAMBILAN PASPOR BERBASIS QR CODE DAN DIGITALISASI ARSIP: SYSTEMATIC LITERATURE REVIEW METODE PRISMA (2019-2025) - Muhammad Andi Anugrah Melanggamasputra; Priati Assiroj; Isidorus Anung Prabadhi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to systematically analyze the development of a QR Code-based passport collection queue application integrated with archive digitization in the context of immigration services. This study employs the Systematic Literature Review (SLR) method with a PRISMA approach to literature published between 2019 and 2025 from the Google Scholar, Scopus, IEEE, and Crossref databases. Unlike previous research that tends to examine queue systems and archive digitization separately, this study emphasizes a comparative synthesis to identify relationships, discrepancies in approaches, and the implications of integrating both systems. The analysis results show that the dominance of conventional approaches, both in terms of development methodology and the technology used, has not yet fully addressed the needs of dynamic public service systems. Additionally, a trade-off was found between system stability and technology flexibility, as well as a significant gap in the integration of QR Code-based queue systems with digital archive management. In the context of passport collection services, this condition implies process inefficiencies, verification redundancies, and limitations in real-time data utilization. This research emphasizes that the development of future immigration service systems needs to adopt an integrated multi-technology-based approach, which combines flexibility, security, and real-time capabilities to comprehensively improve service quality.